Improving the Learning Quality of Math Teachers through the Academic Supervision with Technique of Class Observation - Suparto Suparto (International Research-Based Education Journal, 2020)
Improving the Learning Quality of Math Teachers through the Academic Supervision with Technique of Class Observation. This study aims to find out directly the problems of mathematics teachers and also provides advice, information, and motivation to improve the quality of teaching and learning process, followed by the relevant training based on the problems found and faced by math teachers. This study is a classroom action research using 2 cycles. The results showed that academic supervision with classroom observation techniques can improve the quality of mathematics teacher learning in SMPN 3 Kertosono Nganjuk academic year 2015/2016.